TINGKAT KESEPIAN REMAJA DI PANTI ASUHAN X KOTA PADANG - Dessy Rahmi Utami; Riska Ahmad; Ifdil Ifdil (JURNAL KONSELING GUSJIGANG, 2017)
This study purpose to describe the level of loneliness teenagers in orphanages X Padang city in refer of (1) emotional loneliness, (2) social loneliness, (3) existential loneliness, (4) representational loneliness. The kind of research is descriptive research with quantitative methods. The subject of the study was 32 teenagers who lived in the orphanage X. The instrument used was a lonely teenager scale level. Descriptive analysis with a percentage formula to describe the level of adolescent loneliness. The research findings revealed that (1) the level of lonely teenagers in orphanages X as a whole are generally in middle category (47%), (2) the level of emotional loneliness teenagers at the orphanage X in general are in the medium category (38%), ( 3) the level of social loneliness teenagers in orphanages X in general are in the medium category (34%), (4) the level of existential loneliness teenagers in the orphanage X in general are in the low category (41%), and (5) the level of representational loneliness teenagers in the orphanage X in general are in the medium category (31%). The study recommends to caregivers and administrators of institutions to pay more attention and to understand the problems associated with feelings of teenagers in orphanages and more attention to the psychological needs of adolescents as the need for love, attention, adolescent communication with their families and social needs of adolescents as developing social skills of teenagers. And need counseling services to prevent and cope with feelings of loneliness that arise in adolescents who live in an orphanage.